STATUS PERNIKAHAN WANITA HAMIL DI LUAR NIKAH DALAM PERSPEKTIF IMAM MAZHAB, KHI DAN UU NO 1 TAHUN 1974 - Bahri, Andi Syamsul (Jurnal Ar-Risalah, 2021)
This study discusses the marital status of pregnant women out of wedlock in the perspective of the Imam Madhhab, KHI and Law Number 1 of 1974 concerning Marriage. The purpose of this study was to determine the legal status of a pregnant woman's marriage out of wedlock in the perspective of the Imam Madhhab, KHI and Law no. 1 of 1974 concerning Marriage and to find out the differences and similarities of opinion of the Imams of the Madhhab, KHI, and Law no. 1 of 1974 concerning Marriage, the legal status of a pregnant woman's marriage. The method used in this research is the library method using review and citation techniques. The data obtained were analyzed using qualitative descriptive and content analysis. The approach used is a normative and historical theological approachBased on the results of research according to the madhhabHanafiyah and Syafi'iyah , pregnant women out of wedlock are allowed to marry men who impregnate them. This adulterous behavior does not prevent the validity of the marriage contract. It is different with the madhhab Hambali and Malikiyah, a pregnant woman out of wedlock may not marry a man who impregnates her, nor is it permissible for a man to know that she is pregnant, unless the woman has finished her iddah and has repented. According to Article 53 of KHI, it is explained that a pregnant woman out of wedlock can be married to a man who impregnated her. Meanwhile, according to Law no. 1 of 1974 concerning Marriage does not explain the provisions relating to the marriage of pregnant women, but only regulates the position of children born from the marriage. As explained in the Marriage Law Chapter IX article 42 which reads that a legitimate child is a child born in or as a result of a legal marriage. Meanwhile, in Burgerlijk Wetboek article 32 it is explained that a pregnant woman may not be married to a man who impregnates her and if the marriage does occur, it is considered invalid.